TEACHERS’ CORRECTIVE FEEDBACK ON STUDENTS’ PRONUNCIATION AT THE DAFFODILS ENGLISH COURSE KAMPUNG INGGRIS PARE INDONESIA - Endang Haryanto (Linguists : Journal of Linguistics and Language Teaching, 2015)
Pronunciation is a micro skill of any languages. However, pronunciation is overlooked in the teaching and learning English, and it is not explicitly taught but it is taught in spoken activity in speaking by giving correction on pronunciation errors made they students or corrective feedback. It is one of key in teaching English for EFL learners.This study is aim at describing teachers’ corrective feedback strategies used by the teachers, the timing of corrective feedbacks and their influences on students’ psychological performance during speaking activity at the Daffodils English course . The research design of this research is a case study and the samples of this study were five experience teachers of The Daffodils English Course who are aware of giving corrective feedback on students’ pronunciation. The result of data analysis indicated that there were four types of corrective feedback strategies used by the samples (by the teachers) which involved recast strategies was 58%, metalinguistic was 28.03%, clarification request was 11.21% and elicitation and elicitation was 1.86%. In addition, from total of data, it indicated that the samples gave corrective feedback in two different times that involved immediate and delayed correction. It indicated that 28.03% total of data was immediate correction, and 71.96% data indicated the use of delayed correction.